School- and Leisure Time Factors Are Associated With Sitting Time of German and Irish Children and Adolescents During School: Results of a DEDIPAC Feasibility Study - Lubasch, Johanna Sophie; Thumann, Barbara; Bucksch, Jens; Brackmann, Lara Kim; Wirsik, Norman; Donnelly, Alan; Hayes, Grainne; Nimptsch, Katharina; Steinbrecher, Astrid; Pischon, Tobias; Brug, Johannes; Ahrens, Wolfgang; et al. (Frontiers in Sports and Active Living, 2020)
Objective: The study aims to investigate to what extent school- and leisure time-related factors are associated with sedentary behavior during school in German and Irish children and adolescents. Methods: The study based on a sample of 198 children and adolescents surveyed in 2015. Sedentary and activity behavior were measured using the activPAL physical activity monitor. Information on socio-economic status, school- and leisure-time related factors were provided by questionnaires. Associations between school- and leisure time-related factors and sedentary time during school were estimated using linear multi-level models. Results: Access to play equipment in school was associated with reduced sitting time (hours/day) of children (ß = 0.78; 95%CI = 0.06–1.48). Media devices in bedroom and assessing the neighborhood as activity friendly was associated with increased sitting time of children (ß = 0.92; 95%CI = 0.12–1.72 and ß = 0.30; 95%CI = 0.01–0.60, respectively). The permission to use media devices during breaks was associated with increased sitting time (hours/day) of adolescents (ß = 0.37; 95% CI = 0.06–0.69). A less safe traffic surrounding at school was associated with reduced sitting time of adolescents (ß = −0.42; 95% CI = −0.80 to −0.03). Conclusion: Results suggest that school- and leisure time-related factors are associated to the sedentary behavior during school. We suggest that future strategies to reduce sedentary time should consider both contexts.